An Assessment of the vocational skills of young adults with special needs: basis for transition program : Silahis centers, division of city schools Manila - Villanueva, Nelia D. (Manila : National University, 2008)
This study revolved around the assessment of the vocational skills of the YASNs in three Silahis Centers in the Division Schools of Manila for the academic year 2007-2008. The respondents were previous SPED teachers and at present SPED teachers who are monitoring the YASNs in their activities in the Work Center.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.